An expert-assisted system for improving the quality of IBA simulations by SIMNRA. Issue 1 (1st October 2022) - Mayer, M
Abstract: SIMNRA is a popular software suite for the simulation of ion beam analysis (IBA) spectra. SIMNRA 7.04 implements a new expert system supporting users in selecting the most accurate simulation settings for a given ion/target combination at a given energy and geometry. The expert system is a piece of artificial intelligence emulating the ability and knowledge of a human IBA expert. It points out potential problems with the current simulation parameters and recommends model settings with enhanced accuracy.